Impact of weight reduction on glycemic control and glomerular filtration rate among patients with type 2 diabetic nephropathy - Mahmoud Abd E-Kader, Shehab; AlKhateeb, Afnan M.; AlFawaz, Saad S.; Alabasi, Umar M.; Neamatallah, Ziyad A.; Albadi, Majed; Al-Maddah, Moataz; Hafez, Ammar; Gaowgzeh, Riziq Allah Mustafa; El-Gendy, Salwa R.; El- Banna, Mohamed F.; Alahmadi, Joud Ahmed; et al. (J Med Rehab Sci, 2024)
Background: Diabetic nephropathy is a microvascular diabetic complication affecting about 40% of diabetic patients all over the world. Objective: This study aimed to measure oxidative stress, systemic inflammation and kidney function response to exercise training in type 2 diabetes mellitus (T2DM) nephropathy patients. Material and Methods: Seventy patients T2DM (42 males and 28 females), body mass index (BMI) mean was 32.96 ± 3.25 Kg/m2and the mean of diabetes chronicity was 13.17 ± 2.18 year and enrolled two groups; group I: practiced aerobic exercise training & diet regimen) and group II: practiced no training or diet regimen intervention. Results: There were significant reduction in the mean values of body mass index (BMI), glycosylated hemoglobin (HBA1c), Homeostasis Model Assessment-Insulin Resistance Index) HOMA-IR (, insulin, estimated glomerular filtration rate (eGFR) and creatinine, in the other hand there were significant increase in the mean values of the quantitative insulin-sensitivity check index (QUICKI) in patients of group (A) as a result of weight reducing program, in the other hand the results of the control group (B) were not significant (P<0.05). Conclusion: Weight reducing program modulated glycemic control and renal function of patients with type 2 diabetic nephropathy.